2019
DOI: 10.3390/jcm8111880
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Head and Neck Cancer Organoids Recapitulate EGFR Expression Levels of Respective Tissues and Are Responsive to EGFR-Targeted Photodynamic Therapy

Abstract: Patients diagnosed with head and neck squamous cell carcinoma (HNSCC) are currently treated with surgery and/or radio- and chemotherapy. Despite these therapeutic interventions, 40% of patients relapse, urging the need for more effective therapies. In photodynamic therapy (PDT), a light-activated photosensitizer produces reactive oxygen species that ultimately lead to cell death. Targeted PDT, using a photosensitizer conjugated to tumor-targeting molecules, has been explored as a more selective cancer therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 52 publications
0
80
0
1
Order By: Relevance
“…This last aspect is of particular interest since a local treatment such as PDT, making use of locally applied light at the tumor site, could develop systemic effects via the activation of the immune system. included: the A431 cell line that overexpresses EGFR and the scc-U8 cell line expressing moderate EGFR levels, which more closely resemble the in vivo levels [19,20]. With this in vivo mirroring in mind, a highly cytotoxic NB-PDT (LD100) and a mild treatment (LD50) are also compared here, since uneven light penetration and tumor heterogeneity would likely lead to different degrees of cytotoxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This last aspect is of particular interest since a local treatment such as PDT, making use of locally applied light at the tumor site, could develop systemic effects via the activation of the immune system. included: the A431 cell line that overexpresses EGFR and the scc-U8 cell line expressing moderate EGFR levels, which more closely resemble the in vivo levels [19,20]. With this in vivo mirroring in mind, a highly cytotoxic NB-PDT (LD100) and a mild treatment (LD50) are also compared here, since uneven light penetration and tumor heterogeneity would likely lead to different degrees of cytotoxicity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, isolated cells from the patient are grown as organoids in a 3D matrix, rather than in more traditional 2D culture systems, which better represent in vivo tumor architecture and cell-cell interactions. It has been demonstrated that PDOs from HNC can recapitulate the morphologic and molecular characteristics of the original tumor [33,34]. In addition, PDOs can be readily used to test sensitivity to multiple drugs and radiation due to their relatively rapid 3D culture (i.e., days), compared to the lengthy process of establishing PDXs (i.e., weeks to months) [35].…”
Section: Organoid Modelsmentioning
confidence: 99%
“…In this method, isolated cells from the patient are grown as organoids in a 3D matrix, rather than in more traditional 2D culture systems, which better represents in vivo tumor architecture and cell-cell interactions. It has been demonstrated that PDOs from HNC can recapitulate morphologic and molecular characteristics of the original tumor [28,29]. In addition, PDOs can be readily used to test sensitivity to multiple drugs and radiation due to relatively rapid 3D culture (i.e.…”
Section: Organoid Modelsmentioning
confidence: 99%
“…Humanized mouse models offer a potential solution to this problem as they are immunocompromised to allow for PDX growth, but are then engrafted with a partially functional "human" immune system allowing for the study of the immune response [36]. Humanized animal models offer the opportunity for investigators to study immunomodulatory agents in human cancers (28,(30)(31)(32), work that has taken on greater importance since the 2019 approval of pembrolizumab in the first-line setting for metastatic HNC patients.…”
Section: Humanized Modelsmentioning
confidence: 99%